Student Responses related to Face-to-Face Learning Policies to Overcome Learning Loss Condition - Dedi Riyan Rizaldi; Ziadatul Fatimah; Susilawati Susilawati; Muh. Makhrus (Pascasarjana, Mataram University, 2022)
This study aims to describe student responses and learning outcomes related to the re-implementation of face-to-face learning policies to overcome learning loss conditions. The type of research used is descriptive qualitative research with field research methods, namely collecting data directly from the research site. The sample in this study was 30 students at Madrasah Aliyah Plus Nurul Islam Sekarbela who represented each department (Science and Religion) from grades 10 to 12. The research data obtained consisted of two forms, namely student response data (using a questionnaire) and result from data student learning (using the student's final grade score average). Based on the problems and discussion, it can be seen that the student's response to the re-enactment of face-to-face learning in class is quite good when compared to using an online learning system (learning from home). This is also supported by student learning outcomes using the face-to-face learning system in madrasas that have a higher final average score than during the online learning process.